2021
DOI: 10.3390/ijms22115880
|View full text |Cite
|
Sign up to set email alerts
|

PCSK9 Biology and Its Role in Atherothrombosis

Abstract: It is now about 20 years since the first case of a gain-of-function mutation involving the as-yet-unknown actor in cholesterol homeostasis, proprotein convertase subtilisin/kexin type 9 (PCSK9), was described. It was soon clear that this protein would have been of huge scientific and clinical value as a therapeutic strategy for dyslipidemia and atherosclerosis-associated cardiovascular disease (CVD) management. Indeed, PCSK9 is a serine protease belonging to the proprotein convertase family, mainly produced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
115
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(121 citation statements)
references
References 173 publications
(223 reference statements)
1
115
0
5
Order By: Relevance
“…Targeting PCSK9 using monoclonal antibodies (mAbs) has emerged as an additional and additive therapy to treat hyperlipidaemia due to its regulation of LDLR [28][29][30][31]. However, several recent studies highlighted that PCSK9 can also have various additional effects that are independent of the LDLR, that provide more information on the involvement of PCSK9 in cancer, type 2 diabetes, obesity and several cardiovascular disorders [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Targeting PCSK9 using monoclonal antibodies (mAbs) has emerged as an additional and additive therapy to treat hyperlipidaemia due to its regulation of LDLR [28][29][30][31]. However, several recent studies highlighted that PCSK9 can also have various additional effects that are independent of the LDLR, that provide more information on the involvement of PCSK9 in cancer, type 2 diabetes, obesity and several cardiovascular disorders [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…PCSK9 is a regulatory protein of lipid metabolism that was discovered by Seidah et al in 2003 (31). Its pathogenesis in atherosclerosis and application of inhibitors have been widely studied in recent years (14). Most studies of PCSK9 focused on hepatocytes, promoting LDLR degradation in lysosomes by binding with LDLR, thus increasing plasma LDL-C level.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, PCSK9 has attracted much attention in the field of lipid-lowering because of the powerful reduction of plasma LDL-C levels, amelioration of main adverse cardiovascular events and effect on stabilizing plaques with its inhibition (12,13). In addition to promoting the lysosomal degradation of LDL receptor LDLR on the surface of hepatocytes (14), PCSK9 can also act directly on blood vessel walls, by disrupting lipid intake and efflux of macrophages, promoting the secretion of inflammatory factors and inducing apoptosis to participate in atherosclerosis and even plaque destabilization (15,16). Ding et al (17) found that silencing PCSK9 in THP-1 macrophages could inhibit the formation of foam cells by downregulating the scavenger receptor CD36.…”
Section: Introductionmentioning
confidence: 99%
“…Interaction with the LDLR protein targets LDLR for degradation by the lysosomes and thereby prevents recirculation of LDLR to the cell membrane. To date,~30 GOF variants and another~30 LOF variants are known to be functional, and they are spread over the whole gene [42]. In the Netherlands, those PCSK9 GOF variants were detected in~5% of FH patients, compared to~20% APOB variants and 75% LDLR variants.…”
Section: Screening Beyond Fh; Inclusion Of 24 Additional Genes Of the Cholesterol Metabolismmentioning
confidence: 99%
“…Similarly, in 2017, the variant Gln38Lys in APOC3 has been reported as a possible GOF variant causing hypertriglyceridemia, instead of the well-known LOF mechanisms leading to hypolipoproteinemia [41]. In addition, LOF variants in APOB can cause both hypercholesterolemia or hypobetalipoproteinemia, depending on the type and location of the variant in the gene; missense variants in exon 26 of APOB or nonsense variants in exon 29 lead to hypercholesterolemia, whereas nonsense variants in the first half of APOB cause hypobetalipoproteinemia [42,43]. APOB is a large gene containing many missense variants.…”
Section: Screening Beyond Fh; Inclusion Of 24 Additional Genes Of the Cholesterol Metabolismmentioning
confidence: 99%